Trait Emotional Intelligence and Mathematics Achivements among Undergraduates in Higher Learning Instituition of Sarawak. - Goh, Yi Wen; Tan, Kock Wah (Universiti Malaysia Sarawak (UNIMAS), 2018)
Emotional Intelligence appears to be a significant influencing factor in academic achievements. This study aims to identify the relationship between trait emotional intelligence and mathematics achievements (a relatively sparse research areas of academic achievements) among undergraduates in higher learning institution of Sarawak. 100 respondents from a higher-level institution of Sarawak participated in this study. Trait Emotional Intelligence Questionnaire (TEIQue) is used to measure the trait emotional intelligence of the undergraduates. The result was analysed using descriptive analysis and inferential analysis, namely two-way ANOVA and Pearson’s correlation. Two-way ANOVA was used to test if there is significant difference in demographic attributes (gender and place of residence) towards maths achievements and trait emotional intelligence of the undergraduates. Pearson Correlation was used to test the relationship between trait emotional intelligence and mathematics achievements of the undergraduates. Generally, this study found that there is no significant difference for factors related to demographic attributes (gender and place of residence) against maths achievements and trait emotional intelligence of the undergraduates. Meanwhile, a relationship was found between trait emotional intelligence and mathematics achievements among undergraduates in higher learning institution in Sarawak. The outcome of the study appears to suggest that trait emotional intelligence can help undergraduates to understand themselves more and to control and manage their emotions and feelings and have better relationship with their surroundings. And this could positively impact on their maths achievements